Branched oncolytic peptides target HSPGs, inhibit metastasis, and trigger the release of molecular determinants of immunogenic cell death in pancreatic cancer - Rencinai, Alessandro; Tollapi, Eva; Marianantoni, Giulia; Brunetti, Jlenia; Henriquez, Tania; Pini, Alessandro; Bracci, Luisa; Falciani, Chiara (Frontiers in Molecular Biosciences, 2024)
Immunogenic cell death (ICD) can be exploited to treat non-immunoreactive tumors that do not respond to current standard and innovative therapies. Not all chemotherapeutics trigger ICD, among those that do exert this effect, there are anthracyclines, irinotecan, some platinum derivatives and oncolytic peptides. We studied two new branched oncolytic peptides, BOP7 and BOP9 that proved to elicit the release of damage-associated molecular patterns DAMPS, mediators of ICD, in pancreatic cancer cells. The two BOPs selectively bound and killed tumor cells, particularly PANC-1 and Mia PaCa-2, but not cells of non-tumor origin such as RAW 264.7, CHO-K1 and pgsA-745. The cancer selectivity of the two BOPs may be attributed to their repeated cationic sequences, which enable multivalent binding to heparan sulfate glycosaminoglycans (HSPGs), bearing multiple anionic sulfation patterns on cancer cells. This interaction of BOPs with HSPGs not only fosters an anti-metastatic effect in vitro, as demonstrated by reduced adhesion and migration of PANC-1 cancer cells, but also shows promising tumor-specific cytotoxicity and low hemolytic activity. Remarkably, the cytotoxicity induced by BOPs triggers the release of DAMPs, particularly HMGB1, IFN-β and ATP, by dying cells, persisting longer than the cytotoxicity of conventional chemotherapeutic agents such as irinotecan and daunorubicin. An in vivo assay in nude mice showed an encouraging 20% inhibition of tumor grafting and growth in a pancreatic cancer model by BOP9.